Animal flocking behaviours in game development using FAME - Choy, Jin Xiang (2016)
The Flock Animation & Modeling Environment (FAME) library is a software library package that provides a quick and easy way to realistically model the movements and behaviours of crowds, flocks, and swarms. This library enables the user to easily create flocks, obstacles, and vector fields with configurable properties, thereby decreasing production time and cost. However, the user will still have to spend a significant amount of effort in configuring and manipulating the flocks to have them achieve any recognisable form of behaviour or formation. Also, it is currently only able to create flocks that are defined by 2 dimensional shapes, whereas there are many cases where a 3 dimensional flock is desired. For the library to be attractive to users, it has to provide more in terms of optimizing the workflow when using the library, and also provide needed functionality. Therefore, this project aims to expand the utility of the library and increase its viability through the introduction of pre-set behavioural patterns for flocks that are commonly used, so the user just needs to configure the corresponding pattern instead of creating it by himself. This project will also introduce 3 dimensional flocks and obstacles to the library to widen its range of application. This report identifies various possible flock movement patterns that are commonly seen in areas such as the natural world, video games, and Computer Generated Imagery (CGI). The possible applications of 3D flocks and in extension, 3D obstacles, are also explored. Afterwards, the design and implementation details of the movement patterns, and also of the 3D flocks and obstacles are described and discussed. Finally, at the end of the report, are some recommendations for future work in this area.